A Strategic Approach to Offshoring. (1st October 2013) - Oladi, Reza; Beladi, Hamid; Gilbert, John
<x xml:space="preserve">Abstract</x> In the context of a simple model of strategic offshoring, we investigate the reasons why firms may simultaneously source fragments domestically and internationally. We explore the impacts of offshoring on the production pattern of finished goods, tradable fragment prices, and welfare in a partial equilibrium context. The policy implications of attempts to restrict offshoring are also considered. The analysis shows that an offshoring equilibrium may exist in the absence of comparative advantage in fragments, that offshoring is welfare improving if the costs are sufficiently small, and that attempts (by both countries) to prevent offshoring may paradoxically lower both fragment use and price.